Temperature Dependence of the Non-Stokesian Charge Transport in Binary Blends of Ionic Liquids - Wachter, Philipp; Zistler, Markus; Schreiner, Christian; Fleischmann, Matthias; Gerhard, Dirk; Wasserscheid, Peter; Barthel, Joseph; Gores, Heiner J. (Journal of Chemical and Engineering Data, 2009)
A comprehensive characterization of an ionic liquid based electrolyte for dye-sensitized solar cells (DSSC) was performed by determination of triiodide diffusion coefficients, viscosities, specific conductivities, and densities. The observed non-Stokesian transport behavior was ensured by determination of triiodide diffusion coefficients with two independent methods, steady-state cyclic voltammetry at ultramicroelectrodes, and polarization measurements at thin layer cells. The electrolyte, consisting of 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF_4]), 1-methyl-3-propylimidazolium iodide ([MPIM][I]), and iodine, was examined at fixed iodine concentration over a broad mixing range with varying ionic liquid molar ratio and over a broad temperature range as well. The triiodide diffusion coefficients and the specific conductivity increase with decreasing [MPIM][I] mole fraction or increasing temperature, caused by decreasing electrolyte viscosity. The Einstein-Stokes ratios strongly increase with increasing [MPIM][I] mole fraction and viscosity and thus do not obey the Einstein-Stokes equation. The magnitude of this strong non-Stokesian behavior decreases with increasing temperature. Additional non-Stokesian behavior was found for [MPIM][I]-rich blends since for these blends the Einstein-Stokes ratios strongly decrease at increasing temperatures and simultaneously decreasing viscosity.